How well do randomized trials inform decision making: systematic review using comparative effectiveness research measures on acupuncture for back pain. - Claudia M Witt; Eric Manheimer; Richard Hammerschlag; Rainer Lüdtke; Lixing Lao; Sean R Tunis; Brian M Berman (PLoS ONE)
Background For Comparative Effectiveness Research (CER) there is a need to develop scales for appraisal of available clinical research. Aims were to 1) test the feasibility of applying the pragmatic-explanatory continuum indicator summary tool and the six CER defining characteristics of the Institute of Medicine to RCTs of acupuncture for treatment of low back pain, and 2) evaluate the extent to which the evidence from these RCTs is relevant to clinical and health policy decision making. Methods We searched Medline, the AcuTrials™ Database to February 2011 and reference lists and included full-report randomized trials in English that compared needle acupuncture with a conventional treatment in adults with non-specific acute and/or chronic low back pain and restricted to those with ≥30 patients in the acupuncture group. Papers were evaluated by 5 raters. Principal findings From 119 abstracts, 44 full-text publications were screened and 10 trials (4,901 patients) were evaluated. Due to missing information and initial difficulties in operationalizing the scoring items, the first scoring revealed inter-rater and inter-item variance (intraclass correlations 0.02-0.60), which improved after consensus discussions to 0.20-1.00. The 10 trials were found to cover the efficacy-effectiveness continuum; those with more flexible acupuncture and no placebo control scored closer to effectiveness. Conclusion Both instruments proved useful, but need further development. In addition, CONSORT guidelines for reporting pragmatic trials should be expanded. Most studies in this review already reflect the movement towards CER and similar approaches can be taken to evaluate comparative effectiveness relevance of RCTs for other treatments.